Diffraction and an infrared finite gluon propagator - Luna, E. G. S. (Springer, 2007)
We discuss some phenomenological applications of an infrared finite gluon propagator characterized by a dynamically generated gluon mass. In particular we compute the effect of the dynamical gluon mass on pp and,pp diffractive scattering. We also show how the data on gamma p photoproduction and hadronic gamma gamma reactions can be derived from the pp and pp forward scattering amplitudes by assuming vector meson dominance and the additive quark model.
Keywords: diffractive dissociation; dynamical gluon mass; photoproduction